Implementasi Akad Murabahah pada Produk Pembiayaan BSI KCP Bangkalan dalam Perspektif Hukum Ekonomi Syariah - Ahmad Sirojudin Wildan; Moh. Karim (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
One of the most widely used financing products in Islamic financial institutions is financing based on the murabahah contract. The murabahah contract is a sale and purchase transaction in which the seller states the cost of goods and a profit margin agreed upon with the buyer. This study aims to understand the basic concept of the murabahah contract, its legal basis, and its implementation mechanism. The murabahah contract is a sale and purchase contract that is permitted in Islam as long as it meets the pillars and conditions stipulated in the law of muamalah. Islamic financial institutions act as parties that purchase goods from suppliers and then resell them to customers with an additional agreed profit margin. In its implementation, murabahah financing also has various potential risks, so it is necessary to implement effective risk management so that financing can run safely and in accordance with Islamic principles.